2011
DOI: 10.1021/la104276y
|View full text |Cite
|
Sign up to set email alerts
|

Thermosolutal Self-Organization of Supramolecular Polymers into Nanocraters

Abstract: The ability of two complementary molecular modules bearing H-bonding uracilic and 2,6-(diacetylamino)pyridyl moieties to self-assemble and self-organize into submicrometer morphologies has been investigated by means of spectroscopic, thermogravimetric, and microscopic methods. Using uracilic (3)N-BOC-protected modules, it has been possible to thermally trigger the self-assembly/self-organization process of the two molecular modules, inducing the formation of objects on a mica surface that exhibit crater-like m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…[34,35] We have adopted Suzuki coupling and click chemistry to synthesize the PDPP-Amphi. [7][8][9][10][11][12][13][14][15] In most of the cases, spontaneous self-assembly of organic molecules leads to 1D structures, but preparation of the corresponding 2D sheets of a few layer thickness is a challenge. [36] The thermal properties of PDPP-Amphi were investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) ( Figure S1a ,b, Supporting Information).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[34,35] We have adopted Suzuki coupling and click chemistry to synthesize the PDPP-Amphi. [7][8][9][10][11][12][13][14][15] In most of the cases, spontaneous self-assembly of organic molecules leads to 1D structures, but preparation of the corresponding 2D sheets of a few layer thickness is a challenge. [36] The thermal properties of PDPP-Amphi were investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) ( Figure S1a ,b, Supporting Information).…”
mentioning
confidence: 99%
“…[4][5][6] During the past two decades, supramolecular chemistry has been exploited for the creation of a variety of 0D, 1D, 2D, and 3D nanomaterials. [7][8][9][10][11][12][13][14][15] In most of the cases, spontaneous self-assembly of organic molecules leads to 1D structures, but preparation of the corresponding 2D sheets of a few layer thickness is a challenge. [16][17][18][19] 2D sheets of fluorescent molecules are required for display and sensing applications, however, organic 2D nanosheets having high fluorescence quantum yield is difficult to achieve due to the fluorescence self-quenching.…”
mentioning
confidence: 99%
“…In an another recent report, 170 we have also demonstrated that it is possible to thermally trigger 171 the self-assembly/ self-organisation processes to induce the formation of objects on a mica surface that exhibit crater-like morphologies and a very homogeneous size distribution (Fig. 22).…”
Section: Vesiclesmentioning
confidence: 63%
“…In this way, any changes occurring at one of the two moieties are then reflected on the other. Capitalizing on our previous achievements on the H-bonded uracil·2,6-diamidopyridine complex, we therefore designed and synthesized a photoswitchable uracil–azobenzene derivative presenting direct anchoring of the phenyldiazenyl group to the nucleobase at either the 5- or 6-position ( 5AUP and 6AUP , respectively, Figure ).…”
Section: Resultsmentioning
confidence: 99%